Asta Wirat Bhumi: Musik Eksperimental sebagai Refleksi dan Resepsi Lontar Tutur Bhuwana Mabah - Putu Tiodore Adi Bawa (Journal of Music Science, Technology, and Industry, 2023)
Purpose: This article is about to discuss the process of creating an experimental musical composition entitled Asta Wirat Bhumi which is the result of reflection and reception of the ejection of Tutur Bhuwana Mabah. Method: Creation in Balinese karawitan art becomes very interesting when the exploration of tools and ideas is poured simultaneously. The process of developing Asta Wirat Bhumi uses the theory of creation according to Alma M. Hawkins which consists of the stages of exploration, improvisation, and formation. Asta Wirat Bhumi as a reflection of the Lontar Speech reception of Bhuwana Mabah as an idea for a piece of music that is outlined in Asta Wirat Bhumi's gamelan barungan. Results and discussion: Processed activities starting from exploration, improvisation, and formation to become a reference in a framework that is refined with animating stages. Reflection and reception were chosen as techniques for understanding texts as the ideas of Asta Wirat Bhumi's musical works which are contained in the form/structure of the piece and the performance of the work. Implication: The results obtained are in the form of an experimental musical work "Asta Wirat Bhumi" by casting it in the gamelan barungan "Asta Wirat Bhumi" carrying a message to the audience